AUDIENCE RECEPTION OF MESSAGES IN NANTI KITA CERITA TENTANG HARI INI - Izzaturrahmi, Nabila Khansa; Zahro, Azizatuz (Jurusan Sastra Indonesia, 2023)
When one enjoys a literary work, one gains a new comprehension and impression of the work. Generally, the impression is shaped by the audience’s background, moral beliefs, knowledge, and life experiences. This study aimed to examine audience reception of the message in the film Nanti Kita Cerita Tentang Hari Ini. The analysis stated that the messages found by the moviegoers related to openness of communication in families.